Care in Thatcher’s Times: Douglas Stuart’s ’Shuggie Bain’ (2020) - Alex, Charlotte (undercurrents forum für linke literaturwissenschaft, 2024)
In her article, Charlotte Alex examines how Douglas Stuart’s ’Shuggie Bain’ (2020), which portrays the impact of Thatcherism’s economic and social structures on private relationships of care in Glasgow’s working class, engages with the topic of care. The article argues that Shuggie’s and his mother Agnes’s attempts at caring for each other fail due to a lack of larger structures of responsibility. The novel questions normative definitions of care and shows how the complex and often dysfunctional relationship between the two protagonists counters the era’s rhetoric of individualism.